Penerapan Model Pembelajaran Flipped Learning Dalam Meningkatkan Hasil Belajar Siswa - Asmaul Husna; Sakdiyah; Rahajam; Musfiana; Raihani (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
The aim of this research is to determine the effect of the Flipped Learning learning model on student learning outcomes. This study uses a quantitative approach with a pre-experimental research type. Data collection techniques in this study were using tests, questionnaires, and documentation. While the data analysis technique was the t-test. The results of the study showed that there were differences in student learning outcomes before and after the Flipped Learning learning model was implemented, this can be seen from the t_count value of 11.768 and the sig. value. The results obtained were 0.000 or 0.000 <0.05, so Ho was rejected and Ha was accepted. The results of the student response questionnaire were 91%, which means that the results are included in the very good category. Researchers recommend that schools, especially teachers, prepare a summary of the material in the form of a printout that can be directly distributed to students if there is a power outage. With this alternative, learning activities can continue even though there are technical constraints.